(untitled) (Mustansiria Dental Journal, 2004)
The use of Khat "catha leaves" chewing appear to be finding its way onto the people in Yemen as a socially acceptable and popular habit. Numerous reports have described oral changes that appear to be associated with the use of catha leaves chewing ni adult. A study was therefore undertaken to determine the influence of catha leaves chewing on the mucosa of the oral cavity. Among the total sample of 120 adult habitué, red lesions are identified clinically ni the oral mucosa of six individuals. nI three individuals white lesions are identified at the muccobuccal fold and superficial lesions with color similar to surroundings mucosa was identified in 12 individuals.